2022
DOI: 10.2147/ijgm.s349302
|View full text |Cite
|
Sign up to set email alerts
|

Teachers and Epilepsy in Saudi Arabia: Gaps in Knowledge and Potential Roles

Abstract: In young children, epilepsy, a disorder marked by recurring seizures, is frequent. Schoolteachers play an important role in the development of young children and hence have a big impact on their psychosocial development. This study was carried out to examine the available data from Saudi Arabia in order to better understand the knowledge gap among Saudi instructors. Although schoolteachers’ knowledge in Saudi Arabia has improved over time, such that they now have significant knowledge that can affect student p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 47 publications
(116 reference statements)
2
14
2
Order By: Relevance
“…In contrast, teachers in Riyadh and Khamis Mushait were found to have a high understanding of epilepsy [ 15 , 16 ]. Internationally, teachers' degree of epilepsy knowledge was poor in Kuwait, China, and Italy [ 17 - 19 ]. Although the level of knowledge is insufficient, the understanding and awareness of the etiology of epilepsy have experienced a significant change throughout time.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, teachers in Riyadh and Khamis Mushait were found to have a high understanding of epilepsy [ 15 , 16 ]. Internationally, teachers' degree of epilepsy knowledge was poor in Kuwait, China, and Italy [ 17 - 19 ]. Although the level of knowledge is insufficient, the understanding and awareness of the etiology of epilepsy have experienced a significant change throughout time.…”
Section: Discussionmentioning
confidence: 99%
“…Although the level of knowledge is insufficient, the understanding and awareness of the etiology of epilepsy have experienced a significant change throughout time. Most recent studies have revealed that most teachers believe epilepsy is a neurological disorder [ 19 ]. Consistent with the literature, the current study found that around 86% of teachers agreed that epilepsy is a neurological disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations